Race performance and exercise intensity of male amateur mountain runners during a multistage mountain marathon competition are not dependent on muscle strength loss or cardiorespiratory fitness - Gatterer, H.; Schenk, K.; Wille, M.; Raschner, C.; Faulhaber, M.; Ferrari, M.; Burtscher, M. (The Journal of Strength and Conditioning Research, 2013)
The aims of this study were to quantify the cardiorespiratory fitness level of amateur mountain runners and to characterize the related cardiorespiratory and muscular strain during a multistage competition. Therefore, 16 male amateur participants performed an incremental treadmill test before the Transalpine-Run 2010. Besides race time, heart rate (HR) was monitored using portable HR monitors during all stages, and countermovement jump ability was assessed after each stage. Overall race time and race times of the single stages were not related to any of the cardiorespiratory fitness parameters assessed during the incremental treadmill test (e.g., VO2max, ventilatory threshold). Average HR during the first stage was 81 ± 7% of the maximal HR and decreased to 73 ± 6% during the following stages. Creatine kinase activity as an indirect marker of muscle damage and strain amounted to 1,100 ± 619 U/L after the third stage and was related to the decrease in the mean HR between stage 1 and stage 2 (r = -0.616, p < 0.05). Jump ability decreased continuously in the course of the race but was not related to exercise intensity. In conclusion, this study showed that race performance during a multistage mountain marathon does not depend on cardiorespiratory fitness parameters determined in the laboratory. Furthermore, the mean HR decreased after the first stage and remained constant during the following stages independent of the decreased muscle strength. We interpret these data to mean that performance differences were a result of insufficient recovery after the first day of multistage mountain running and the different individual pacing strategies. It is worth mentioning that also other factors, not determined in this investigation, could be responsible for the present outcomes (e.g., nutrition, genetics, psychological and environmental factors, or different training programs).